Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha
Wydawnictwo:Nowa Era
Rok wydania:2016
Uporządkuj sumy algebraiczne S i T 4.43 gwiazdek na podstawie 7 opinii

`a)` 

`S=x^3-2x^2+3x^5-4=` `3x^5+x^3-2x^2-4` 

`T=3x^2-2x^4+4-x^3=-2x^4-x^3+3x^2+4` 

 

`S+T=(3x^5+x^3-2x^2-4)+(-2x^4-x^3+3x^2+4)=` 

`\ \ \ \ \ \ \ \ \ = 3x^5+x^3-2x^2-4-2x^4-x^3+3x^2+4=` 

`\ \ \ \ \ \ \ \ \ =3x^5-2x^4+x^2` 

 

`S-T=(3x^5+x^3-2x^2-4)-(-2x^4-x^3+3x^2+4)=` 

`\ \ \ \ \ \ \ \ \ =3x^5+x^3-2x^2-4+2x^4+x^3-3x^2-4=` 

`\ \ \ \ \ \ \ \ \ =3x^5+2x^4+2x^3-5x^2-8` 

 

 

 

`b)` 

`S=1/2x^4-1/3x^3+x-3x^2=1/2x^4-1/3x^3-3x^2+x` 

`T=3x^2-x-3/2x^4+2/3x^3=` `-3/2x^4+2/3x^3+3x^2-x` 

 

`S+T=(1/2x^4-1/3x^3-3x^2+x)+(-3/2x^4+2/3x^3+3x^2-x)=` 

`\ \ \ \ \ \ \ \ \ =1/2x^4-1/3x^3-3x^2+x-3/2x^4+2/3x^3+3x^2-x=` 

`\ \ \ \ \ \ \ \ \ =-x^4+1/3x^3` 

 

`S-T=(1/2x^4-1/3x^3-3x^2+x)-(-3/2x^4+2/3x^3+3x^2-x)=` 

`\ \ \ \ \ \ \ \ \ =1/2x^4-1/3x^3-3x^2+x+3/2x^4-2/3x^3-3x^2+x=` 

`\ \ \ \ \ \ \ \ \ =2x^4-x^3-6x^2+2x`